Janus kinase (JAK) inhibitors for the treatment of skin and hair disorders: a review of literature. (18th August 2017) - Samadi, Aniseh; Ahmad Nasrollahi, Saman; Hashemi, Ashkan; Nassiri Kashani, Mansour; Firooz, Alireza
Abstract: Janus kinase family (JAKs) has recently attracted the attention of many researchers, and several JAK inhibitor drugs have been developed targeting different members of the JAK family. Tofacitinib and ruxolitinib are US FDA approved drugs in this family for rheumatoid arthritis and myeloproliferative diseases, respectively. Dysregulation of JAK/STAT pathway is also involved in many skin diseases, specifically inflammatory disorders. The JAK/STAT signaling pathway and its involvement in skin diseases are overviewed in this study. We also review clinical studies of JAK inhibitors in field of dermatology, including psoriasis, atopic dermatitis, alopecia areata and vitiligo. Although the available evidence shows promising results, it is still too early to draw a firm conclusion about the place of these drugs in dermatological treatment.